Long-term trends in the prescription of antidiabetic drugs: real-world evidence from the Diabetes Registry Tyrol 2012–2018. Issue 1 (1st September 2020) - Engler, Clemens; Leo, Marco; Pfeifer, Bernhard; Juchum, Martin; Chen-Koenig, Di; Poelzl, Karin; Schoenherr, Hans; Vill, David; Oberdanner, Juliana; Eisendle, Egon; Middeldorf, Klaus; Heindl, Bernhard; et al.
Abstract : Introduction: Prescription patterns of antidiabetic drugs in the period from 2012 to 2018 were investigated based on the Diabetes Registry Tyrol. To validate the findings, we compared the numbers with trends of different national registries conducted in a comparable period of time. Research design and methods: Medication data, prescription patterns, age groups, antidiabetic therapies and quality parameters (hemoglobin A1c, body mass index, complications) of 10 875 patients with type 2 diabetes from 2012 to 2018 were retrospectively assessed and descriptively analyzed. The changes were assessed using a time series analysis with linear regression and prescription trends were plotted over time. Results: Sodium/glucose cotransporter 2 inhibitors (SGLT-2i) showed a significant increase in prescription from 2012 to 2018 (p<0.001), as well as metformin (p=0.002), gliptins (p=0.013) and glucagon-like peptide-1 agonists (GLP-1a) (p=0.017). Significant reduction in sulfonylurea prescriptions (p<0.001) was observed. Metformin was the most frequently prescribed antidiabetic drug (51.3%), followed by insulin/analogs (34.6%), gliptins (28.2%), SGLT-2i (11.7%), sulfonylurea (9.1%), glitazones (3.7%), GLP-1a (2.8%) and glucosidase inhibitors (0.4%). Conclusions: In this long-term, real-world study on prescription changes in the Diabetes Registry Tyrol, we observed significant increase in SGLT-2i, metformin, gliptins and GLP-1a prescriptions. In contrast prescriptions for sulfonylureas declined significantly. Changes were consistent over the years 2012–2018. Changes in prescription patterns occurred even before the publication of international and national guidelines. Thus, physicians change their prescription practice not only based on published guidelines, but even earlier on publication of cardiovascular outcome trials.